Postinfarction Hearts Are Protected by Premature Senescent Cardiomyocytes Via GATA4‐Dependent CCN1 Secretion. Issue 18 (18th September 2018) - Cui, Sumei; Xue, Li; Yang, Feihong; Dai, Shuai; Han, Ziqi; Liu, Kai; Liu, Baoshan; Yuan, Qiuhuan; Cui, Zhaoqiang; Zhang, Yun; Xu, Feng; Chen, Yuguo
Abstract : Background: Stress‐induced cell premature senescence participates in a variety of tissue and organ remodeling by secreting such proteins as proinflammatory cytokines, chemokines, and growth factors. However, the role of cardiomyocyte senescence in heart remodeling after acute myocardial infarction has not been thoroughly elucidated to date. Therefore, we sought to clarify the impact of premature myocardial senescence on postinfarction heart function. Methods and Results: Senescence markers, including p16 INK 4a, p21 CIP 1/ WAF 1, and SA‐β‐gal staining, were analyzed in several heart disease models by immunostaining. Both postinfarction mouse hearts and ischemic human myocardium demonstrated increased senescence markers. Additionally, senescence‐related secretory phenotype was activated after acute myocardial infarction, which upregulated senescence‐related secretory phenotype factors, including CCN family member 1 (CCN1), interleukin‐1α, tumor necrosis factor α, and monocyte chemoattractant protein‐1. In vivo, a tail vein injection of AAV9‐ Gata4 ‐shRNA significantly attenuated senescence‐related secretory phenotype secretion and aggravated postinfarction heart dysfunction. Furthermore, among activated senescence‐related secretory phenotype factors, CCN1 administration reduced myofibroblast viability in vitro and rescued the deleterious effect of AAV9‐ Gata4 ‐shRNA in vivo. Conclusions: Myocardial premature senescence was observed in the ischemic hearts and improved postinfarction heart function, partly through the GATA‐binding factor 4‐CCN1 pathway.